Influence of Different Concentrations of Calcium Pectate on Ripening of Tomato Lycopersicon esculentum L - Jagatheeswari, D (International Journal of Pharmaceutical & Biological Archive, 2013)
Influence of Different Concentrations of Calcium Pectate on Ripening of Tomato Lycopersicon esculentum L